Optical properies of crosslinked chitosan thin film with glutaraldehyde using surface plasmon resonance technique - Yap, Wing Fen; Mat Yunus, Wan Mahmood; Abd. Moksin, Mohd Maarof; Talib, Zainal Abidin; Yusof, Nor Azah (Science Publications, 2011)
Problem statement: The aim of this research is to study the optical properties of crosslinked chitosan thin film with glutaraldehyde using Surface Plasmon Resonance (SPR) technique. Approach: The crosslinked chitosan is synthesized by homogeneous reaction of medium molecular weight chitosan in aqueous acetic acid solution with glutaraldehyde as crosslinking agent. Four different amount of chitosan, i.e., 0.40, 0.50, 0.60 and 0.70 g of chitosan, were dissoloved in 50 ml acetic acid separately. Glass cover slips (as substrates) were first coated with two sets of different thickness of gold layer. Then the amount of 0.55 mL of each crosslinked chitosan solution was spin coated onto the gold layer. Results: Using developed multilayer Matlab fitting program (matrix method based), the experimental surface plasmon resonance curves were fitted to obtain the thickness and refractive index of crosslinked chitosan thin film. The real and imaginary part of refractive index of crosslinked chitosan thin film are (1.540 ± 0.005) and (0.015 ± 0.002), respectively. Conclusion: The results are similar for all different thickness of the thin films and not affected by the thickness of gold layer. This study is important for future research on multilayer SPR sensor.